Quality of life in elderly people with diabetes mellitus and systemic arterial hypertension - Evangeline Maria Cardoso; Thaliê Cavalcante Santos; Fernando José Herkrath; Taciana Lemos Barbosa (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2023)
Abstract Background: Systemic arterial hypertension (SAH) and diabetes mellitus (DM) are grievances that are sensitive to the measures of promotion and prevention; however, they interfere with the quality of life (QL). Objective: The aim of this study was to evaluate the QL in elderly people with SAH and DM and compare their impact on the QL of these groups. Method: It was used as a methodology a sectional, domiciliary-based study in which the data were collected using a questionnaire with sociodemographic information, clinical and QL, through the WhoQol-Bref and analyzed in the SPSS software. Results: A total of 498 elderly people were evaluated, of whom 9.64% had DM, 53.21% had SAH, and 37.15% had both diseases. The majority were women (66.9%), from 60 to 69 years old (49.4%), mixed race (61.6%), from 9 to 11 years of study (53%), family budget under two minimum wages (48.6%), married (52.8%), and using five or more medications (18.9%). There was a difference among the groups (SAH, QL, or both) in the physical domain (p=0.003) and in the social relationships (p=0.017). In the physical domain, the post hoc tests showed better QL in SAH groups compared to the others. Conclusions: The patients with SAH showed better general QL. The psychological domain was the least affected and the environment domain was the most affected.